Biblijny szafan – problem identyfikacyjno-egzegetyczny - Morta, Krzysztof (Verbum Vitae, 2017)
The article discusses the hyrax (dassie), a small Biblical creature which over the centuries has caused translators and exegetes of the Bible many problems of identification (see Lev. 11:5; Deut. 14:7; Psalm 104:18; Prov. 30:26). Early in this process, in place of the otherwise unknown Hebrew term saphan the Septuagint translators introduced a likewise not widely-known Greek equivalent, choirogrillios. This inevitably gave rise to several different identifications, with references to the hare, hedgehog, or even hog. Over time, the resultant Biblical exegesis, based on compounded inaccuracies and misunderstandings, introduced still other misinterpretations. In this way, the one Hebrew word saphan began to be perceived as two distinct animals and commented upon as a hedgehog and a hare (Augustine). A reverse phenomenon also occurred, whereby the features of two different animals used as saphan equivalents were actually combined into one composite creature (St. Jerome). Nevertheless, the present article attempts to organise all the relevant information concerning the identification of saphan. It also lists testimonies, preserved in texts of the Church Fathers, indicating that in their day the hyrax had in fact already been identified. Unfortunately, due to the creature’s limited geographical range, the readers/audience of the Bible were not usually familiar with this animal. That is why accurate information about the hyrax has not been spread and used more widely. Thus, the complicated issues concerning saphan present challenges, even today, to the researchers, scholars and authors wishing to write about it.